The Impact of Multiculturalism on Trade in Medieval Islam: The Azerbaijani Case - Mirzabayova, Roya (Sunan Kalijaga: International Journal of Islamic Civilization, 2024)
Islamic civilization in the Middle Ages, the period of cultural, economic, and scientific development called the "Golden Age of Islam", has been a real source of pride for the Muslim world. As a high and dominant civil society, medieval Islamic civilization has now gone through the process of integration, where different cultures and minorities have merged into a single society with the condition that each of them preserves their own roots and creates a unique environment of coexistence. Several factors shaped coexistence in Islamic civilization. The first factor is the emergence of the Islamic religion in the 7th century. The second factor is the multitude of economic ties between the countries included in the Islamic world. Muslims understood that the basis of the economy was trade. The spread of Islam from the Middle East to China, from North Africa to the centres of Europe, developed trade. In the Middle Ages, Azerbaijan became one of the leading countries where trade developed due to its location at the crossroads of trade routes from East to West, which became important for the Caliphate. Thus, the multicultural environment created by the Arab Caliphate created a foundation for the development of trade in Azerbaijan, making this country an important point for the coexistence and welfare of peoples. The article studies the trade relations of Azerbaijan during the Middle Ages, the impact of the multicultural environment on trade, and the development of trade within the framework of the economic relations established with other countries. As for the research methods used in the study, a number of factors that play a key role in the economic development of Azerbaijan have been studied by preserving the principle of historicity, a comparative analysis of trade relations through historical-excursion.